Efficacy of a reading and language intervention for children with Down syndrome: a randomized controlled trial. - Burgoyne, K; Duff, F; Clarke, P; Buckley, S; Snowling, M; Hulme, C (2012)
BACKGROUND: This study evaluates the effects of a language and literacy intervention for children with Down syndrome. METHODS: Teaching assistants (TAs) were trained to deliver a reading and language intervention to children in individual daily 40-min sessions. We used a waiting list control design, in which half the sample received the intervention immediately, whereas the remaining children received the treatment after a 20-week delay. Fifty-seven children with Down syndrome in mainstream primary schools in two U.K. locations (Yorkshire and Hampshire) were randomly allocated to intervention (40 weeks of intervention) and waiting control (20 weeks of intervention) groups. Assessments were conducted at three time points: pre-intervention, after 20 weeks of intervention, and after 40 weeks of intervention. RESULTS: After 20 weeks of intervention, the intervention group showed significantly greater progress than the waiting control group on measures of single word reading, letter-sound knowledge, phoneme blending and taught expressive vocabulary. Effects did not transfer to other skills (nonword reading, spelling, standardised expressive and receptive vocabulary, expressive information and grammar). After 40 weeks of intervention, the intervention group remained numerically ahead of the control group on most key outcome measures; but these differences were not significant. Children who were younger, attended more intervention sessions, and had better initial receptive language skills made greater progress during the course of the intervention. CONCLUSIONS: A TA-delivered intervention produced improvements in the reading and language skills of children with Down syndrome. Gains were largest in skills directly taught with little evidence of generalization to skills not directly taught in the intervention.